2022
DOI: 10.3390/ijms231810344
|View full text |Cite
|
Sign up to set email alerts
|

Role of Innate and Adaptive Cytokines in the Survival of COVID-19 Patients

Abstract: SARS-CoV-2 is a new coronavirus characterized by a high infection and transmission capacity. A significant number of patients develop inadequate immune responses that produce massive releases of cytokines that compromise their survival. Soluble factors are clinically and pathologically relevant in COVID-19 survival but remain only partially characterized. The objective of this work was to simultaneously study 62 circulating soluble factors, including innate and adaptive cytokines and their soluble receptors, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
(133 reference statements)
3
7
0
Order By: Relevance
“…It should be noting that proinflammatory cytokines induced by viral infection may modulate lipid metabolism [ 21 ]. Our study found increased secretion of pro-inflammatory cytokines such as CCL20/MIP3ɑ, IL-10, IL-15, IL-27 in non-survivors than in controls that is consistent with previously published data (Supplementary materials) [ 22 ]. Also, our finding is that increased expression levels of LDL receptors genes ( LDLR , CD36 , STAB1 ) were found in non-survivors and survivors compared to controls at time to admission to the ICU.…”
Section: Discussionsupporting
confidence: 93%
“…It should be noting that proinflammatory cytokines induced by viral infection may modulate lipid metabolism [ 21 ]. Our study found increased secretion of pro-inflammatory cytokines such as CCL20/MIP3ɑ, IL-10, IL-15, IL-27 in non-survivors than in controls that is consistent with previously published data (Supplementary materials) [ 22 ]. Also, our finding is that increased expression levels of LDL receptors genes ( LDLR , CD36 , STAB1 ) were found in non-survivors and survivors compared to controls at time to admission to the ICU.…”
Section: Discussionsupporting
confidence: 93%
“…CCL20/MIP3ɑ mainly elicits its effector function via CCR6 receptor binding; interestingly enough, we previously noted a negative correlation between CCR6 ex-pressing CD8+ cells and IL-27 [31]. However, secretion of IL-15 and IL-27 was increased in non-survivors compared to both survived patients and controls that is consistent with previously published data [32]. It is interesting to note that IL-15 and IL-27 are early cytokines, and this change in their concentration indicates the activation of the innate immune response when the virus is recognized by the epithelial or dendritic cells of the body, followed by the induction of the innate defense of body and induction of inflammation processes [31,[33][34].…”
Section: Discussionsupporting
confidence: 92%
“…It is interesting to note that IL-15 and IL-27 are early cytokines, and this change in their concentration indicates the activation of the innate immune response when the virus is recognized by the epithelial or dendritic cells of the body, followed by the induction of the innate defense of body and induction of inflammation processes [31,3334]. In accordance with our and previous data, IL-15, IL-27 were previously associated with the severity and fatal outcome of COVID-19 [32, 3538]. Additionally, we revealed the negative correlation between concentration of these cytokines and key lipid parameters (TC, LDL, HDL), in particular, LDL cholesterol level, and this correlation was more pronounced after 7 days in the patient subgroup with fatal outcome.…”
Section: Discussionsupporting
confidence: 87%
“…Among others, severe COVID-19 patients present with elevated circulating levels of IL-6, TNFα, IL-1β, IFNγ and others, 38 and the levels are often correlated with COVID-19 severity. [50][51][52][53][54] Some patients develop a cytokine release syndrome and even a cytokine storm, which can be fatal as it can result in an acute respiratory distress syndrome (ARDS) and multiple organ dysfunction (MOD). 55 Taken together, the current knowledge indicates that a successful immune response (leading to fast elimination of the virus and a full recovery) relies on an efficient and wellcoordinated immune response involving all parts of the immune system.…”
Section: Immunity To Sars-cov-2 Infectionsmentioning
confidence: 99%